2019
DOI: 10.31235/osf.io/xn9uj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

After Coming Out: Parental Acceptance of Young Lesbian and Gay People

Abstract: This study examines extant scholarly knowledge on parental acceptance of young lesbian and gay people in traditional heteronormative families. Recent literature shows that parents generally accept their lesbian and gay children. However, parents do not always accept them immediately after they come out. Acceptance takes time, and transitioning to acceptance is often a complex process that depends on parents’ access to the necessary resources for coping with the stresses of knowing that their child identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 52 publications
(134 reference statements)
0
9
0
Order By: Relevance
“…36A few scholars have started to pay attention to homonormativity in relation to the family in Asia, including in Chinese societies (including mainland China, Hong Kong and Taiwan) (Luo 2020; 2021a; 2021b; Kong 2011; 2020; Brainer 2019; Wei and Yan 2021), India (Ghosh 2020) and Singapore (Phillips 2014). However, there is still a lack of effort, overall, to theorize Asian homonormative stories or study homonormativity in “the specific conditions in which gay people live their lives” (Brown 2012, 1069) in the non-Western world.…”
mentioning
confidence: 99%
“…36A few scholars have started to pay attention to homonormativity in relation to the family in Asia, including in Chinese societies (including mainland China, Hong Kong and Taiwan) (Luo 2020; 2021a; 2021b; Kong 2011; 2020; Brainer 2019; Wei and Yan 2021), India (Ghosh 2020) and Singapore (Phillips 2014). However, there is still a lack of effort, overall, to theorize Asian homonormative stories or study homonormativity in “the specific conditions in which gay people live their lives” (Brown 2012, 1069) in the non-Western world.…”
mentioning
confidence: 99%
“…Researchers explored LGBTQ+ youth's 30 experiences of coming out to their parents —both, from the perspective of the child (e.g., Cramer & Roach, 1988; Enck et al., 1984; Potoczniak et al., 2009; Rossi, 2010; Savin‐Williams, 1989; Švab, 2016) and parent (e.g., Alpaslan et al., 2014; Butauski & Horstman, 2020; Mirkovic & Jerkovic, 2021)—and explored parents' reactions and acceptance development of their child's coming out (e.g., Cassar & Sultana, 2021; Chrisler, 2017; Drumm et al., 2021; Goodrich & Ginicola, 2017; Jaspal, 2020; Mayeza, 2021; Pullen Sansfaçon et al., 2020; van Bergen et al., 2020). Acceptance development and similar terms such as ‘family adjustment’ or ‘acceptance journey’ refer to findings that suggest that despite common parental reactions of shock, surprise, confusion, and stress (Ghosh, 2020) that can lead to negative consequences for the disclosing individual, 31 initial negative parental reactions can develop into acceptance and support.…”
Section: Three‐lens Typologymentioning
confidence: 99%
“…This includes massive amounts of publications within multiple disciplines that focus on different coming out aspects. Authors have provided overviews of coming out research sub‐areas, for example, of parental acceptance after coming out (Ghosh, 2020), the coming out process of LGB individuals in families (Alonzo & Buttitta, 2019), or as part of publication introductions. However, no one has ever provided an overview of the entire coming out research field, an overview that is needed if we want to better understand its development and reach.…”
Section: Introductionmentioning
confidence: 99%
“…Rudwick's (2010) study participants revealed how some of their families would slaughter livestock and perform rituals in with the hope of their becoming "real men". After several failed attempts, it was often the women who accepted their family member's gay identities (Ghosh, 2020;Khaxas & Frank, 2013;Ryan, 2009). For centuries the debate over the place of homosexuality in Christianity has been and still is an issue (Nkosi & Masson, 2017;Ravhuhali, Maluleke, Mboweni & Nendauni, 2019).…”
Section: Religious and Cultural Normsmentioning
confidence: 99%
“…However, being rejected affects people differently. Globally, at least 51% of LGBTI youth have experienced discrimination within their families, often through socio-emotional rejection along with economic sanctions (Ghosh, 2020). As noted by Abou-Chadi and Finnigan, (2019), because of their sociocultural beliefs, some families will not only disown the homosexual family member, but those who are seen to be supporting them also face possible rejection.…”
Section: Family Rejectionmentioning
confidence: 99%